Pengaruh Disiplin Terhadap Kinerja Karyawan CV. Metassa Collection Di Kabupaten Serang - Soleh Rosyad; Badru Sobirin; Hurriyah Agustini (E-Journal Studia Manajemen, 2014)
The success of a company is reflected in each individual discipline within the company, if the discipline of employees in a company is low, will affect the performance of the employee, it is because disciplinary effect on performance. The purpose of this study was to analyze the influence of discipline on performance. This study uses a quantitative approach. The sampling technique using saturated sample amounted to 35 respondents. The results of this study are: There is a positive and significant effect on discipline in performance.